IMPLEMENTASI LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MODEL DISCOVERY LEARNING (DL) PADA MATA PELAJARAN BIOLOGI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI MIA 9 SMAN 1 PEKANBARU TAHUN AJARAN 2017/2018 - Wulandari, Sari; Natalina L, Mariani; Darmadi, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract :This research aimed to improve critical thinking skills of student class XI MIA 9 SMA Negeri 1 Pekanbaru by implementation worksheets based on Discovery Learning model. It had been done in SMA Negeri 1 Pekanbaru on Maret-May 2018. Parameters measure were student’s critical thinking skill, studen’t achievement and student’s attitude. The methods of this research was classroom action research by implementation worksheets based on Discovery Learning model. It had been done in two cylce. There were planning step, acting step, observation step and reflection step for each cycle. The research instrument used was a learning device that consist of a lesson plan, syllabus, assesment authentic sheet, observation sheet and critical thinking skill sheet. The collected data was analysed descriptively. The result of this research showed that critical thinking skill on first cycle was 82,94 (C) and increased on second cycle up to 89,47 (B). Student’s achievement on first cycle was 81,95 (C) and increased on second cycle up to 84,15 (A). Classical completeness percentage on first cycle was 87,87 (B) and increased on second cycle up to 100%. Student’s attitude on first cycle was 83,04 (C) and increased on second cycle up to 90,39 (B). It can be conclude that worksheets based on Discovery Learning model can improve critical thingking skill of student class XI MIA 9 SMA Negeri 1 Pekanbaru.Key Words : Worksheets, Discovery Learning Critical, Thinking Skills